(untitled) (Eurasian Scientific Herald, 2022)
A method is a set of measures and measures used to overcome a certain obstacle in achieving a goal in the pedagogical process. There are several, sometimes dozens, of methods of overcoming obstacles in achieving a goal that are used in a particular system. The system of methods used to achieve a goal is called a method (path). In the process of applying the methods in a certain style, the status of each action is subject to certain target indicators. In addition, a person also applies a number of laws as a principle in the process of achieving a goal. This article discusses the features of the innovative organization of pedagogical processes